Outbreak of freckle disease (Phyllosticta cavendishii) on Cavendish bananas in Australia and the initial biosecurity response. (14th November 2019) - McMaster, C. A.; Tran‐Nguyen, L. T. T.; Voutsinos, M. Y.; Cook, S. E.; Condé, B. D.; West, S. J.; Nguyen, T. V.; Liberato, J. R.
Abstract : Phyllosticta cavendishii has been recorded in the Northern Territory (NT) of Australia occurring on non‐Cavendish bananas since 1991. The race of P. cavendishii that infects Cavendish bananas is considered exotic to Australia and classified as an emergency plant pest. In July 2013, P. cavendishii was detected on Cavendish bananas near Darwin, NT. Here, the diagnoses and field observations carried out during the Incident Definition Phase of the national biosecurity response, from July 2013 to October 2014, are reported. Of 1395 banana samples collected from 676 properties, 480 were positive for freckle disease, including 463 samples with P. cavendishii and 17 samples with P. maculata . Phyllosticta cavendishii was detected in 256 properties, including 62 properties where it was detected on Cavendish banana plants, within six distinct geographical zones across the NT. Phyllosticta cavendishii was detected on two cultivars within the Cavendish subgroup and six non‐Cavendish cultivars. Multigene characterization of Phyllosticta cultures showed that P. cavendishii was isolated from both Cavendish and non‐Cavendish cultivars. Multilocus phylogeny analyses also revealed that the P. cavendishii strain in the outbreak had identical sequence similarity to the holotype (CBS H‐20918) clade 2 P. cavendishii isolates that infect both Cavendish and non‐Cavendish cultivars in Southeast Asia and Oceania. The genetic data in this study showed that there was one P. cavendishii strain infecting both Cavendish and non‐Cavendish cultivars in the outbreak. However, historical data and field observations provided anecdotal evidence for the existence of two races of P. cavendishii, including one that does not infect Cavendish bananas.